Extensive Assessment of Underlying Etiological Factors in Primary Infertile Men Reduces the Proportion of Men With Idiopathic Infertility - Ventimiglia, Eugenio; Pozzi, Edoardo; Capogrosso, Paolo; Boeri, Luca; Alfano, Massimo; Cazzaniga, Walter; Matloob, Rayan; Abbate, Costantino; Viganò, Paola; Montorsi, Francesco; Salonia, Andrea (Frontiers in Endocrinology, 2021)
Objective Up to 40% of infertile men remain without a recognized cause (i.e., idiopathic infertility). We aimed to identify, categorize, and report the supposed causes of male infertility in a cohort of white-European men presenting for primary couple’s infertility, by using a thorough and extensive baseline diagnostic work-up. Material and Methods Cross-sectional study of 1,174 primary infertile men who underwent a thorough diagnostic work-up including: detailed medical history, physical examination, hormonal assessment, genetic testing, semen analyses; semen and urine cultures; testis color Duplex US. Men without any identified causal factor were considered as idiopathic. Six different etiological categories were established, and their prevalence was estimated. Logistic regression models estimated the risk of missing causal identification. Results A possible causal factor was identified in 928 (81%) men. Hypogonadism was the most frequent identified cause (37%), followed by varicocele (27%). Genetic abnormalities were found in 5% of patients. A causal factor was more easily identifiable for the more severe infertility cases, and azoospermic men were those less likely to be defined as idiopathic (OR and 95% CIs: 0.09; 0.04-0.20). Relative proportion of identified causes remained constant during the 10-year study period (p>0.43). Conclusions Due to a more comprehensive and extensive diagnostic work-up, at least one underlying cause of male infertility factor in 4 out of 5 infertile men can be identified. Men with a less severe phenotype remain a clinical challenge in terms of establishing a possible etiologic factor. Further studies are needed to assess which subset of infertile men deserves a more extensive work-up.